Gambaran Tingkat Kecemasan Anak Prasekolah Berdasarkan Frekuensi Hospitalisasi di Ruang Anak Rumkit TK II Prof. dr. J.A Latumeten Ambon - Ernawati Hatuwe; Mirdat Hitiyaut; Rahma Tunny (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background Anxiety is confusion, worry about something that will happen with an unclear cause. For preschool children, being sick and hospitalized is a terrible new thing, they accept this situation as a sense of fear, even some of them will refuse to be hospitalized. The purpose of this study was to describe the level of anxiety of preschool children based on the frequency of hospitalization in the children's room of Rumkit TK.II.Prof.Dr.J.A. Latumeten Ambon. The design of this study is a quantitative descriptive study. Sampling using the Accidental Sampling technique with a sample size of 30 respondents. Data collection was obtained through the Spance Children's Anxiety Scale (SCAS) instrument. This study was taken in the Children's Room of Rumkit TK II.Prof.Dr.J.A.Latumeten Ambon. The results of this study were that those who were hospitalized for the first time were 16 respondents (53.3) and a small number of respondents had experienced a history of previous hospitalization or ≥ 2 times as many as 14 respondents (46.7). For the level of anxiety, most respondents experienced severe anxiety as many as 11 respondents (36.7), moderate anxiety as many as 8 respondents (26.7) and a small number of respondents experienced panic as many as 2 respondents (6.7). Conclusion The level of anxiety of preschool children when first hospitalized is severe anxiety, the level of anxiety of preschool children who are hospitalized ≥ 2 times is categorized as severe anxiety and moderate anxiety.